Pemanfaatan Limbah Sampah Berbasis Reduce, Reuse, Recycle di Desa Roa Kecamatan Detusoko Kabupaten Ende - Tola, Damianus; Banda, Yosef Moan; Amrin, Sayful (LPPM Universitas Flores, 2023)
The problem that causes the increase in plastic waste generated by all elements of society is one of the environmental problems that are difficult to solve properly. Waste management is very necessary to minimize the negative impacts and future challenges. Waste management needs to be carried out in a comprehensive and integrated manner so that people and the environment become healthy and are able to change the behaviour of local people in general. This activity was attended by 31 psychology students selling economic education at the University Flores class of 2021 implementation of activities to utilize waste based on reduction, recuse, and recycling in roa village Detusoko district Ende Regency. The creator team formed by students of economics education at the University of Flores is motivated by a spirit of critical thinking in developing their talents as people of change. The management stage is in the form of assembling and manufacturing practices by a group of students from the faculty of economics at the University Flores, by assembling various shapes that have been cut to become a flower that is of use value and decoration for the living room. Overcoming environmental pollution requires the intention and sincerity of al roa village people in general and being aware of the moral responsibility of people who feel they are perpetrators or causes of environmental pollution. The Roa village community must instil disciplined behaviour in handling the disposal of organic solid waste originating from household activities.